2019
DOI: 10.7189/jogh.09.010503
|View full text |Cite
|
Sign up to set email alerts
|

Increasing coverage of pediatric diarrhea treatment in high-burden countries

Abstract: Background Diarrhea is the second leading cause of infectious deaths in children under-five globally. Oral rehydration salts (ORS) and zinc could avert an estimated 93% of deaths, but progress to increase coverage of these interventions has been largely stagnant over the past several decades. The Clinton Health Access Initiative (CHAI), along with donors and country governments in India, Kenya, Nigeria, and Uganda, implemented programs to scale-up ORS and zinc coverage from 2012 to 2016. The progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…We found that of the 526 800 diarrhoeal deaths (95% UI 485 300-568 900) estimated to have occurred in 2017 in children younger than 5 years across the 94 LMICs included in our analysis, an estimated 299 900 deaths (274 000-324 300) could be attributable to lack of treatment with ORS. We also estimated that increase in ORS coverage during the study period prevented an additional 52 In a sensitivity analysis, we found that, while the geographical patterns in deaths averted remained largely unchanged, the absolute number of averted deaths changed substantially in some places (appendix 1 pp 82-83). Reducing the percentage of diarrhoeal deaths that could be averted with ORS from 69% to 35% reduced the total number of deaths attributable to lack of ORS Dark grey grid cells were classified as barren or sparsely vegetated and had fewer than ten people per 1 km × 1 km grid cell; light grey countries were not included in these analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that of the 526 800 diarrhoeal deaths (95% UI 485 300-568 900) estimated to have occurred in 2017 in children younger than 5 years across the 94 LMICs included in our analysis, an estimated 299 900 deaths (274 000-324 300) could be attributable to lack of treatment with ORS. We also estimated that increase in ORS coverage during the study period prevented an additional 52 In a sensitivity analysis, we found that, while the geographical patterns in deaths averted remained largely unchanged, the absolute number of averted deaths changed substantially in some places (appendix 1 pp 82-83). Reducing the percentage of diarrhoeal deaths that could be averted with ORS from 69% to 35% reduced the total number of deaths attributable to lack of ORS Dark grey grid cells were classified as barren or sparsely vegetated and had fewer than ten people per 1 km × 1 km grid cell; light grey countries were not included in these analyses.…”
Section: Resultsmentioning
confidence: 99%
“…49 In addition, promoting zinc use has shown a secondary effect of increasing ORS use in some places; 50,51 thus comprehensive approaches to overcome challenges to uptake and scaling up of coverage are warranted. 52 Future work could investigate how missing data affect estimates of ORS coverage and how to account for this, as well as how to incorporate differences between urban and rural populations into the analysis. In addition, we did not map ORS availability, but rather the prevalence of its use, and future studies could map availability distribution patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Some high-burden countries have established successful scale-up programmes to increase coverage and access rates of ORS and zinc supplementation among target population groups [8,24]. Paediatric diarrhoeal treatment rates in Kenya increased from 0.8 to 15% in 5 years after permission was given to dispense zinc supplements over-the-counter and government procurement was shifted to co-packaged ORS and zinc.…”
Section: Discussionmentioning
confidence: 99%
“…Paediatric diarrhoeal treatment rates in Kenya increased from 0.8 to 15% in 5 years after permission was given to dispense zinc supplements over-the-counter and government procurement was shifted to co-packaged ORS and zinc. These policies created a competitive market for ORS and zinc supplements and enhanced healthcare provider practices in the management of diarrhoeal diseases [24].…”
Section: Discussionmentioning
confidence: 99%
“…The CHAI interventions included improving knowledge about appropriate treatment for caregivers via schools and community health workers and for providers via education and mentorship as well as drug detailing. Extensive work was needed to increase the availability of affordable ORS and zinc products and establish a functional supply chain, as well as assist with policies, such as approving zinc as an over-the-counter medicine and adding it to the national essential medicines list [17]. An important strategic activity in these countries was the change from separate ORS and zinc products to a co-packaged product, particularly in the public sector [15].…”
mentioning
confidence: 99%